2002
DOI: 10.1007/s00213-001-0955-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the effects of alcohol on driving-related psychomotor skills by chronic exposure to cannabis

Abstract: For psychomotor skills relevant to driving, chronic cannabis use (in the absence of acute administration) does not potentiate the effects of alcohol. In fact, the superior tracking accuracy of regular users relative to infrequent users after alcohol, and their lower scores for dizziness, suggest that chronic cannabis use may instead confer cross-tolerance to specific effects of alcohol on behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, previous notions (Marks and MacAvoy 1989; Wright and Terry 2002) that chronic cannabis use would also develop cross-tolerance for the impairing effects of alcohol were not confirmed. It should be noted however that previous studies never demonstrated complete tolerance to the behaviorally impairing effects of alcohol in heavy cannabis users.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, previous notions (Marks and MacAvoy 1989; Wright and Terry 2002) that chronic cannabis use would also develop cross-tolerance for the impairing effects of alcohol were not confirmed. It should be noted however that previous studies never demonstrated complete tolerance to the behaviorally impairing effects of alcohol in heavy cannabis users.…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, BACs were generally lower than those obtained in the present study after repeated alcohol dosing. For example, Wright and Terry (2002) tested tracking performance of heavy cannabis users within 30 min after drinking while mean BACs declined from 0.28 to 0.22 mg/ml. Mean BAC levels in the present study however were two to three times as high and experimentally controlled to achieve relatively steady state levels during 5 h of repeated performance testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent cannabis smokers demonstrate tolerance to some acute cannabis intoxication effects (Ramaekers et al, 2011), but tolerance did not compensate for all effects (Downey et al, 2013). There is currently substantial interest in comparing occasional to frequent smokers and assessing potential tolerance (Ramaekers et al, 2009; Toennes SW et al, 2008; Wright and Terry, 2002), especially as medical and recreational cannabis becomes more commonplace.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prolonged combined impact of alcohol and cannabis, research has proposed that persistent or lingering effects of cannabis could result in crosstolerance to certain impairing alcohol effects (sleep outcomes not examined, [15,16]). Conversely, a recent study discovered that cannabis users experienced decreased negative feelings following alcohol consumption compared to non-cannabis users [17], indicating possible cross-sensitisation.…”
mentioning
confidence: 99%